THE EFFECT OF ELEY RIDEAL MECHANISM ON CO-NO CATALYTIC SURFACE REACTION FOR A HEXAGONAL LATTICE: A MONTE CARLO SIMULATION STUDY - Qaisrani, A. U.; Khalid, M.; Naz, Samina; Ullah, M. G. (The Nucleus, 2011)
A Monte Carlo simulation for CO-NO heterogeneous catalytic reaction over a square lattice as well as hexagonal lattice has already been performed with a model based on the Langmuir- Hinshelwood mechanism. Similarly this reaction on square lattice has also been studied by Eley-Rideal mechanism. Here Monte Carlo simulation has been used to study the effect of Eley-Rideal mechanism on a hexagonal lattice for CO-NO reaction. The reactive window gets enhanced due to this mechanism. It is observed that whenever ER mechanism is introduced, the production of CO2 and N2 starts as soon as the CO partial pressure (yCO) departs from zero, which verifies the experimental observation. Moreover, the maximum production rate increases with the increase of ER probability.